PIXE facility at Centro Atómico Bariloche - Limandri, Silvina Paola (2014)
A Tandem accelerator, NEC Pelletron 5SDH, has been recently installed at Centro Atómico Bariloche, Argentina. This facility provides to the local scientific community the opportunity to use nuclear techniques (PIXE, RBS, PIGE, ERDA and ion channeling) in different fields involving material characterization. This communication includes a brief description of the system facility with the main associated equipment, in particular that used for PIXE measurements. In addition, we show some recent applications of PIXE performed at our laboratory.